2017
DOI: 10.1155/2017/1785217
|View full text |Cite
|
Sign up to set email alerts
|

Different Types of Physical Activity and Fitness and Health in Adults: An 18-Year Longitudinal Study

Abstract: Objective. The aim of this study is to examine the relationship between different types of daily life physical activity (PA) and physical fitness (PF) and health throughout adulthood. Methods. A total of 723 men and women, aged 28–76 years, participated 1681 times during four measurement points from 1992 to 2010 in this study. We assessed self-reported PA, anthropometrics, physical health status (HS), and PF in each study year. Hierarchical linear modeling (HLM) was used to analyze the measures. Results. PF an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 44 publications
(57 reference statements)
4
36
0
7
Order By: Relevance
“…[9][10][11] Several studies have shown that physically active adults are healthier and have a higher PF than inactive adults throughout different nations and populations groups. [11][12][13] PA is therefore promoted as part of a healthy lifestyle. [14] The current understanding of the relationship between PA, PF, and health can be visualized using the model from Bouchard et al, and the model illustrates that PA can influence fitness and health and that the relationships are also reciprocal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] Several studies have shown that physically active adults are healthier and have a higher PF than inactive adults throughout different nations and populations groups. [11][12][13] PA is therefore promoted as part of a healthy lifestyle. [14] The current understanding of the relationship between PA, PF, and health can be visualized using the model from Bouchard et al, and the model illustrates that PA can influence fitness and health and that the relationships are also reciprocal.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] The regular physical activity (PA) can improve PF and health as prevention disease problem. [9][10][11] Several studies have shown that physically active adults are healthier and have a higher PF than inactive adults throughout different nations and populations groups. [11][12][13] PA is promoted as part of a healthy lifestyle.…”
Section: National Journal Of Physiology Pharmacy and Pharmacologymentioning
confidence: 99%
“…Ebenfalls thematisieren keine Studien den Einfluss von längsschnittlichen Veränderungen der sportlichen Aktivität (Aktivitätskarrieren) auf die längsschnittlichen Veränderungen von Fitness und Gesundheit. [6,7]. Vergleicht man körperlich-sportliche Aktive mit Inaktiven, so sind die Aktiven im mittleren Erwachsenenalter motorisch rund 10 Jahre jünger.…”
Section: Projekthistorieunclassified
“…Hier stellt sich außerdem die Frage, inwiefern die Ergebnisse der Studie deutschlandweit verallgemeinerbar sind. Bad Schönborn gilt als repräsentativ hinsichtlich der soziodemografischen Rahmendaten für eine rurale Gemeinde in Deutschland, wobei die körperliche Aktivität im Vergleich zu anderen Studien leicht über dem deutschen Mittel liegt [6]. Detaillierte Analysen zum Drop-Out ergaben, dass die Verzerrungen aufgrund von selektivem Nonresponse jedoch relativ gering sind.…”
Section: Diskussionunclassified
See 1 more Smart Citation